Analysis of dynamic changes in retinoid-induced transcription and epigenetic profiles of murine Hox clusters in ES cells - De Kumar, Bony; Parrish, Mark E.; Slaughter, Brian D.; Unruh, Jay R.; Gogol, Madelaine; Seidel, Christopher; Paulson, Ariel; Li, Hua; Gaudenz, Karin; Peak, Allison; McDowell, William; Fleharty, Brian; et al.

(untitled) (Genome Research, 2015)
The clustered Hox genes, which are highly conserved across metazoans, encode homeodomain-containing transcription factors that provide a blueprint for segmental identity along the body axis. Recent studies have underscored that in addition to encoding Hox genes, the homeotic clusters contain key noncoding RNA genes that play a central role in development. In this study, we have taken advantage of genome-wide approaches to provide a detailed analysis of retinoic acid (RA)-induced transcriptional and epigenetic changes within the homeotic clusters of mouse embryonic stem cells. Although there is a general colinear response, our analyses suggest a lack of strict colinearity for several genes in the HoxA and HoxB clusters. We have identified transcribed novel noncoding RNAs (ncRNAs) and their cis-regulatory elements that function in response to RA and demonstrated that the expression of these ncRNAs from both strands represent some of the most rapidly induced transcripts in ES cells. Finally, we have provided dynamic analyses of chromatin modifications for the coding and noncoding genes expressed upon activation and suggest that active transcription can occur in the presence of chromatin modifications and machineries associated with repressed transcription state over the clusters. Overall, our data provide a resource for a better understanding of the dynamic nature of the coding and noncoding transcripts and their associated chromatin marks in the regulation of homeotic gene transcription during development.